Intellectual Capital in the Context of Strategic Business Development - Broniukaitis, Romualdas (Buhalterinės apskaitos teorija ir praktika, 2018)
[only abstract in English; full article and abstract in Lithuanian] The need to establish themselves in a dynamic and complex business environment urges organisations to look for innovations that would foster business development. Organisations are forced to continuously develop and improve new strategies for competitive advantage, flexibility and innovativeness. The aim to succeed in a complex and heterogeneous environment leads to the approach that the most valuable organisational resource is its intangible assets – its employees’ knowledge and skills. Maintaining the level of these assets and integrating them into organisation’s activities becomes the critical factor in strategic business development. Theoretical approach and the central assumption of this study is that intangible resources are a strategic asset that plays the key role in creating long-term competitive advantage. The article aims to demonstrate the importance of intellectual capital and its influence on strategic business development. The article develops a new understanding of business development in a long-term perspective by emphasising the importance of the interrelationship between intellectual capital and its elements for organisational success. The article highlights the importance of a strategic approach to holistic management of intangible resources in pursuit of organisational effectiveness. The article uses methods of literature review, comparative analysis and synthesis.